2017
DOI: 10.9734/jamps/2017/32384
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Breast Diseases in Nigeria North Central: A Histopathological Survey

Abstract: Breast diseases to most patients are sources of uncertainty and apprehension. The diseases of the breast are a heterogeneous group of lesions consisting of both benign and malignant. This study from North Central Nigeria is aimed at examining these diverse lesions. 249 breast biopsies with histopathological diagnosis seen at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
2
5
3
Order By: Relevance
“…The most common quadrant involved was upper outer, which included 34.5% of the carcinomas, followed by central quadrant (25.5%), which was comparable to the studies by Anushree et al [14] (upper outer 30% and central 17%), and Jangid et al [13] (upper outer 30.19%). Among the various histological types, the most common in our study was IDC NST (86.4%), which corresponds with studies by Anushree et al [14] (60%), Yogalakshmi et al [11] (77%), Eke et al [15] (88.6%) and Nandam et al [12]. 90.9% cases showed tumor size more than 2 cm, which was close to Ambroise et al study (91.5%) [16].…”
Section: Discussionsupporting
confidence: 91%
“…The most common quadrant involved was upper outer, which included 34.5% of the carcinomas, followed by central quadrant (25.5%), which was comparable to the studies by Anushree et al [14] (upper outer 30% and central 17%), and Jangid et al [13] (upper outer 30.19%). Among the various histological types, the most common in our study was IDC NST (86.4%), which corresponds with studies by Anushree et al [14] (60%), Yogalakshmi et al [11] (77%), Eke et al [15] (88.6%) and Nandam et al [12]. 90.9% cases showed tumor size more than 2 cm, which was close to Ambroise et al study (91.5%) [16].…”
Section: Discussionsupporting
confidence: 91%
“…At the national level, only the South-West, South-South and North-Central Nigeria had cases of Paget's disease. Its prevalence in Ogun State (South-West) was higher than that recorded in Delta State (South-South) [13] but lower than that reported in Benue State, North-Central [15]. The prevalence of medullary carcinoma in this study was higher than that reported in Maiduguri [18] and Warri [13] but lower than that reported in Lagos [10], Benin [14] and Zaria [20].…”
Section: Discussioncontrasting
confidence: 73%
“…In this study, the prevalence of breast cancer among other human cancers was lower (40.9%) than the value recorded in Abuja (50.8%) [22] and Osun State (53.2%) [23] and higher than the value reported in Kwara State (22.4%) [24], Borno State (13.9%) [18] and Benue State (8.1%) [15], but comparable with the value recorded in Oyo State (40.8%) [22]. This suggests that females in South-West Nigeria are relatively at a higher risk of developing breast cancer than any other region in Nigeria.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations